PERAN GREEN PERCEIVED QUALITY MEMEDIASI HUBUNGAN ANTARA ENVIRONMENTAL FRIENDLINESS DENGAN GREEN TRUST - Dewi Kartika, Ni Putu Eka; Suparna, Gede (E-Jurnal Manajemen; Vol 6 No 5 (2017), 2017)
The purpose of this study was to clarify the role of green perceived quality in mediating influence the environmental friendliness to the green trust on cosmetics product The Face Shop. This research location in Denpasar city the samples used were 120 respondent. Data were collected by distributing questionnaires directly and using Likert scale. Data analysis technique used is comfirmatori factor analysis, path analysis and test Sobel. The analysis showed that the environmental friendliness significantly and positive affect green perceived quality dan green trust. Green perceived quality significantly mediates the relationship between the environmental friendliness to the green trust. It means the opportunities for the companies to package products or environmental friendliness bussiness strategy that will have an impact on consumer confidence in eco-friendly products.
Keywords: green marketing, environmental friendliness, green perceived quality, green trust